Implied cases for Muslim same-sex unions - Jahangir, Junaid (My University, 2010)
Concerning contemporary homosexuality, are we Moslems reading the holy verses and Hadith in a way that calls upon all our knowledge and spiritual resources? Putting aside extreme penalties, mainstream Muslim opinions on the subject of how our communities should deal with homosexuality are made up of counseling reparative therapy and marriage or prescribing celibacy. Neither scientific consensus nor human suffering seems to have motivated a re-evaluation of the Muslim scriptures. While inter-sexuals have been accommodated by the highest of both Sunni and Shia scholarly bodies, gays and lesbians continue to be viewed as having made a deliberate morally wrong choice.
Keywords: homosexuality; religion; Islam